Sentential Negation in North-eastern Gallo-Romance dialects: insights from the Atlas Linguistique de la France. Issue 2 (July 2019) - Burnett, Heather
Abstract: This article argues that data from the Atlas Linguistique de la France (ALF, Edmont and Gilliéron, 1902 –1910 ) can shed light on the fine-grained syntax of sentential negation in the Oïl dialects spoken in North Eastern France, Belgium and Switzerland. The Gallo-Romance dialects spoken in this area possess a larger variety of negative structures than those found in (Standard) French: in addition to ne…pas, ne can be followed by negations mie, pont or even appear alone. Although the dialects under study are highly endangered, I show how we can use syntactic data 'hidden' in the ALF to study their syntactic patterns. I present a quantitative study of variation in sentential negation in authentic transcriptions and French translations of the 22 negative data points in the ALF at 150 points in France, Belgium and Switzerland (N = 2989). I show that the pont form is significantly more frequent in negative constructions with 'weak NPs' ( de phrases) and that there is a significant correlation between dropping of secondary negation and the ability of the secondary negation mie to be realized as an enclitic -m . This study supports Dagnac (2018 )'s conclusion that the ALF is an invaluable tool for the study of syntactic microvariation in France.